Energy and Water Monitoring for a Large Social Housing Intervention in Northern Italy - Filippi, Marco; Sirombo, Elisa (Frontiers in Energy Research, 2019)
In recent years, the awareness of the problem of the performance gap and rebound effect extends the interest in assessing the real operation of buildings, in assessing how buildings match users' needs once they are occupied and in understanding how occupants’ behavior affects the actual building performance. The paper discusses the case study and presents the results of a monitoring campaign of two years of occupancy of a large social housing intervention recently built near Milan, for a total of 152 flats. Data about the thermal energy consumption for heating and cooling, the domestic hot and cold water use and the occupants’ intervention on controlling devices are assessed and presented. The case study is representative of the actual design and construction of high performing multi-family buildings in Italy. All the buildings are class A rated, very highly insulated and ventilated with centralized mechanical ventilation systems with thermodynamic heat recovery. Centralized water-to-water heat pumps supply hot and refrigerated water for heating and cooling and domestic hot water as well. A building monitoring system is installed, able to track energy and water consumption, factors influencing the energy consumption not related to the building characteristics (weather data, operational setting) as well as the overall building performance data. The results show unexpected high energy and water consumption and moreover a large variability of the energy and water consumption pattern among the dwellings and between the years due to the significant influence of the occupants’ behavior and habits.